Innexin and pannexin channels and their signaling. Issue 8 (14th March 2014) - Dahl, Gerhard; Muller, Kenneth J.
Abstract : Innexins are bifunctional membrane proteins in invertebrates, forming gap junctions as well as non‐junctional membrane channels (innexons). Their vertebrate analogues, the pannexins, have not only lost the ability to form gap junctions but are also prevented from it by glycosylation. Pannexins appear to form only non‐junctional membrane channels (pannexons). The membrane channels formed by pannexins and innexins are similar in their biophysical and pharmacological properties. Innexons and pannexons are permeable to ATP, are present in glial cells, and are involved in activation of microglia by calcium waves in glia. Directional movement and accumulation of microglia following nerve injury, which has been studied in the leech which has unusually large glial cells, involves at least 3 signals: ATP is the "go" signal, NO is the "where" signal and arachidonic acid is a "stop" signal.